Stakeholder Perspectives on the Value of Marine Spatial Planning Towards Advancing Offshore Wind in the U.S. Issue 3 (4th May 2019) - Ryan, Kendra; Bates, Alison; Gopnik, Morgan; Danylchuk, Andy; Jordaan, Adrian
Abstract: The United States contributes only 0.2% of the 18, 814 MW of global installed offshore wind capacity. Lack of development has been attributed in part to a cumbersome regulatory process that includes the evaluation of environmental impacts. Assessments are based on biological, social, and technical data that are often incomplete. Marine spatial planning (MSP) may help fill data gaps. We conducted semi-structured interviews with key informants to understand (1) whether a lack of biological data impedes offshore wind environmental assessments, (2) whether MSP could mitigate these impediments, and (3) whether MSP could advance offshore wind development in the U.S. in other ways. Most informants stated that a lack of biological data in offshore wind environmental assessments was problematic due to incomplete data, uncertainty of data, and mismatched scales. Data issues may be mitigated by creation of data products and increased communication, outcomes of MSP that may benefit the regulatory process by increasing data availability, resolving conflicts among users, and providing a common operating picture. Challenges remain in integrating MSP into the processes of siting and permitting offshore wind, but it provides a strategic framework for the systematic identification, collection, collation, analyses, application, and management of data in the offshore wind environmental regulatory process.